Management control system and governance practices in NGOs - Ibrahim, Suraiya; Md Shabudin, Amirul Shah; Soo, Jin Cheah (2015)
This paper forms part of a major research into the development of the management control system and governance practices in a Malaysian non-government organization (NGO).Since NGOs play an important role in the Malaysian community, they are expected to be effective and efficient in management control system and governance in order to achieve targeted goals.Using the new institutional sociology as the theoretical underpinning, this study seeks to understand why and how management control systems and governance practices emerge in the way they do within the Malaysian environment.This paper is the result of a preliminary literature review on management control systems and governance practices commonly undertaken in both for-profit as well as not-for-profit organizations in general.